Hubungan Hipertensi dengan Kejadian Katarak pada Lansia di Poli Mata RSUD dr. M. Yunus Bengkulu - Ida Rahmawati; Loren Juksen; Jopi Ishan Putra (Jurnal Kesehatan dr. Soebandi, 2018)
Cataract is eye disease which can cause low vision and blindness. Blindness cases are highest in Indonesia and in the World due to cataract. Cataract could be happened because of degenerative factors that can be influenced by aging. Hypertension is either degenerative disease due to free radicals and decrease in antioxidant so that, can increase of lens opacity.This research aims to know the relationship between hypertension on elderly in Outpatient Eye Care Dr. M Yunus Hospital, Bengkulu Province, years 2018. This technic research used cross sectional. The subject in this research is all of elderly with cataract who getting treatment in Outpatient Eye Care Dr. M. Yunus Bengkulu. The sampling technique uses proportional systematic sampling, obtained 90 respondents. Statistical tests using chi-square (X2). To determine the closeness of the relationship using Contingency Coefficient (C). The result of this research obtained; a) there were 29 respondents (32.2%) with hypertension and 61 respondents or 67.8% without hypertension; b) there were 27 respondents (30.0%) with mature cataract and 63 respondents or 70.0% with immature cataract. The result of Chi Square Analysis obtained p= 0.279 < α = 0.05 meaning there is no relationship between hypertention and cataract